Long-term non-conditional and conditional metastasis of uveal melanoma by tumor size category in 8034 patients - Rolika Bansal; Hidayet Sener; Jerry A Shields; Carol L Shields (Indian Journal of Ophthalmology)
Purpose: To estimate metastasis of patients with uveal melanoma (UM) based on tumor size categories classified by ultrasonographic thickness as small (0.0–3.0 mm), medium (3.1–8.0 mm), or large (≥8.1 mm) using both non-conditional and conditional analyses. Design: Retrospective analysis. Methods: A retrospective study of 8034 cases over 35-years at a single ocular oncology referral center evaluated the primary endpoint of cumulative incidence of metastasis at 5-, 10-, 15-, 20-, 25- and 30-years using non-conditional and conditional analysis at 3-years, 5-years, and 10-years of metastasis-free survival. Results: The mean thicknesses for small, medium, and large UMs were 2.5 mm, 5.0 mm, and 10.2 mm, respectively. Based on tumor size category (small vs. medium vs. large), the 25-year non-conditional metastasis was 5% vs. 12% vs. 21%, and for those with 3-year metastasis-free survival, the 25-year incidence of metastasis was 7% vs. 13% vs. 26%. For those with 5-year metastasis-free survival, the 25-year incidence of metastasis was 6% vs. 11% vs. 21%. For those with 10-year metastasis-free survival, the 25-year incidence of metastasis was 4% vs. 8% vs. 21%. For small vs. medium UM, by conditional analysis, those who maintained 3-year/5-year/10-year metastasis-free survival, hazard ratio was 1.50 (P <0.01)/1.53 (P <0.01)/1.77 (P = 0.01), and for medium vs. large UM, hazard ratio was 1.45 (P <0.01)/1.44 (P = 0.03)/1.96 (P = 0.06). Conclusion: Long-term comparative analysis of UM metastasis, based on tumor size category (thickness) as small, medium, or large, revealed that large UM is more likely with higher tendency to develop metastasis over time. The patients achieving 3-, 5-, and 10-year metastasis-free survival demonstrated significantly reduced subsequent risk of metastasis across all tumor size categories.